Analisis pemanfaatan fitur Track Changes pada MS.Word untuk mengetahui originalitas karya Mahasiswa - Seituni, Siti; Yuliana, Dyan; Suparto, Arico Ayani; Rahmawati, Weni Kurnia; Febriyanti, Anis (Academy of Education Journal, 2024)
Analysis on the benefits of technology has a good impact if users understand the benefits or usefulness of a feature. in learning is a complete element that underlies the usefulness in providing techniques, especially in a scientific work. One of the most commonly used word processing programmes is Microsoft Word, which has a "track changes" feature that allows users to track changes made to documents. The track changes feature is needed in educational institutions that require students to submit written work in digital form so that the use of this feature is very effective. The purpose of this study is to determine the use and results of the analysis of the Track Changes Feature in Ms. Word so as to determine the Originality of Student Work. This type of research uses qualitative research with a descriptive approach, the main data sources in qualitative research are words and actions. (2-tailed) 0.00 <0.05, it can be concluded that there is a significant difference between students who have been given the Track Changes Feature in Ms. Word to Know the Originality of Student Work. This research concludes that the Track Changes feature has a good and useful impact in making student assignments, so it needs to be analyzed further so that it can be disseminated to courses or to all course lecturers at STKIP PGRI Situbondo.